l-DOPA and Its Receptor GPR143: Implications for Pathogenesis and Therapy in Parkinson’s Disease - Goshima, Yoshio; Masukawa, Daiki; Kasahara, Yuka; Hashimoto, Tatsuo; Aladeokin, Aderemi Caleb (Frontiers in Pharmacology, 2019)
L-3,4-Dihydroxyphenylalanine (L-DOPA) is a most effective therapeutic agent for Parkinson’s disease (PD). L-DOPA is traditionally believed to be an inert amino acid that exerts actions and effectiveness in PD through its conversion to dopamine. In contrast to this generally accepted idea, L-DOPA is proposed to be a neurotransmitter. Recently, GPR143 (OA1), the gene product of ocular albinism 1 was identified as a receptor candidate for L-DOPA. GPR143 is widely expressed in the central and peripheral nervous system. GPR143 immunoreactivity was colocalized with phosphorylated -synuclein in Lewy bodies in PD brains. GPR143 may contribute to the therapeutic effectiveness of L-DOPA and might be related to pathogenesis of PD.